Library and Information Science Education and Dissemination of Agricultural Information for Sustainable Development in Nigeria - Adamu, Mohammed Saba; Babalola, Gideon A.; Dogara, Ladan (MiddleBelt Journal of Library and Information Science, 2020)
This paper examined the indispensability of library and information science education as the major pivot upon which sustainable development in agriculture in Nigeria and globally is hinged. Literature, which are relevant to the paper were searched. Access to relevant, current and up to date agricultural information is crucial to maximum output of rural farmers. In this information driven age, the use of ICT devices could be reliable especially mobile phones in disseminating relevant and current agricultural information to rural farmers with a view to boosting their productivity. Rural farmers, however need a kind of pedagogy so as to benefit fast from the avalanche of information formats that are made available with ICT and its applications. The paper recommended that the Federal Government of Nigeria should follow suit with developed countries such as China to design agricultural information dissemination models. Example of such models may include but not limited to Web Portal, Voice-Based Service, Text (SMS)-Based Service, Self-Support Online Community, Interactive Video Conferencing Service, Mobile Internet-Based Service and Unified Multi-Channel Service Model.